(untitled) (Encuentros, 2021)
The article presents some results after integrating Instagram as a virtual learning environment for the teaching of visual and plastic arts to ninth-grade students. Some objectives of the research were the design of usage guidelines for such integration, the development of a curriculum that effectively integrated the social network, and the evaluation of significant experiences throughout the artistic practice. Research of a qualitative nature was developed thanks to the action-research method which made it possible to integrate each research aspect together with the application of different techniques and instruments typical of the method used. Some results highlighted were the use of Instagram in each creative process, the design of conceptualized narratives for social networks, the promotion of collaborative and critical learning, and unexpected aspects of the problem of identity in networks.